Child first, offender second – A progressive model for education in custody. (September 2020) - Case, Stephen; Hazel, Neal
Abstract: Disengagement and poor educational attainment in education are firmly established risk factors for juvenile crime, leading policymakers to identify educational provision in and after custody as a key pathway for effective reentry (resettlement). However, although there is emerging evidence that children's educational progress can reduce recidivism, persistent issues have dogged the delivery of education in custody across the Western world. We identify these issues as rooted in fundamental weaknesses of the risk paradigm that defines the relationship between custodial education and juvenile justice outcomes, in particular reflecting the absence of a cogent theory of change. We propose an alternative 'Child First' conceptual framework for custodial education that draws on the 'Positive Youth Justice' approach in contemporary youth justice and adopts the development of children's pro-social identity as its theory of change and key purpose. We explore for the first-time what overarching principles such an approach might entail and test the appropriateness of its theory of change by using it to reinterpret existing good practice messages for custodial education. Therefore, we propose a thoroughgoing evaluation of custodial education practice through such a 'Child First' lens.